Plant Bridge: Connecting Separated Objects Using Plant Growth - Kodai Ochi; Mitsuharu Matsumoto (Biomimetics)
In recent years, there has been development in bio-hybrid actuators that utilize living organisms themselves, as opposed to biomimetics. However, most of the plants and animals used for these purposes are no longer actually alive, as their corpses, parts, or seeds are used. There is research on the use of microorganisms, but it is limited to use in building materials. Here, we focused on plants in terms of their ease of growth with water and light and their ability to change shape significantly from seed through growth. Therefore, we propose a material that incorporates living plants. The objective of this research is to realize the shape change of this material by using the property of plants to grow toward light. In the experiment, we confirmed that plants growing from two devices cross-linked between the devices by controlling the direction of growth using peas. The bridged plants did not break when a mass of up to 575 g was placed on it and indicated a load-bearing capacity of more than 6.6 times from the mass ratio. Then, it is demonstrated that the robot could cross over that.